(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Wound infections are major obstacle in wound healing process, associated with extended hospital stay, increases hospitalization and treatment cost. The antimicrobial spectrum varies from place to place with respect to time, population and kind of pathogenic strains causing infection. Prolonged wound infection can be life threatening along with the comorbidities and Biofilm formation by infecting pathogens. Biofilms are capable of evolving and disseminating antimicrobial resistance amongst these pathogens contributing to overall antimicrobial treatment failure. Hence, it is very crucial to detect biofilm production capacity of the infecting pathogen along with antimicrobial susceptibility pattern. Aim: To study Clinico-microbiological profile, microbial prevalence and antimicrobial susceptibility profile with in-vitro biofilm production capacity of the wound infection isolates reported in Microbiology laboratory of Central Diagnostic Laboratory, Shree Krishna Hospital. Material and Method: This prospective cross-sectional study was conducted from November 2020 to December 2020. The wound isolates were identified by culture identification methods (Vitek 2 Compact), antimicrobial susceptibility test (Vitek 2 Compact) and biofilm production capacity done by 96 well micro-titer plate method (using spectrophotometer). Results: From 100 wound isolate, 44 wound isolates were culture positive. Staphylococcus aureus was the major bacterial isolate (36.3%), followed by E. coli being the second predominant (18.1%). Among Staphylococcus aureus 7(43.7%) of them were found to be methicillin resistant Staphylococcus aureus (MRSA). The extended spectrum beta lactamase producers (ESBL) among E. coli were 2(28.7%). All the 44 wound isolates were tested for their Biofilm producing capacity, from which 32(72.7%) wound isolates were biofilm formers and 12 (27.3%) were biofilm non-formers. Conclusion: This study has shown that a majority of the isolates were gram positive bacteria and there is a need for continuous monitoring to determine the susceptibility pattern of the common isolates which are found in the hospital. According to which the policies on prescription to be reviewed, which will reduce the patient’s hospital stay, health and treatment cost. Also the prevalence of biofilm producer isolates were significant, hence the choice of antimicrobial agent need also to be done keeping this local prevalence in consideration.